Magnetic model of light in moving media and effects of the Aharonov-Bohm type - Spavieri, Gianfranco; Gillies, George (Ciencia, 1970)
The magnetic model of light in moving media is considered here in relation to the electromagnetic interaction momentum that is linked to the Fresnel-Fizeau term. Applications of the magnetic model extend from gravitation to water waves. We show that the validity of the model might require that photons in moving media are not affected by the flow or that particles in the Aharonov-Bohm effect are dragged by the electromagnetic interaction. PACS: 03.30.Óp, 03.65.Ta.